What Is over and above Psychopathy? The Role of Ability Emotional Intelligence in Predicting Criminal Behavior. Issue 1 (2nd January 2017) - Curci, Antonietta; Cabras, Cristina; Lanciano, Tiziana; Soleti, Emanuela; Raccis, Carla
Abstract : This study aims to investigate the role of ability emotional intelligence (EI) in predicting criminal behavior from a life-span perspective, over and above psychopathy. Psychopathic individuals are characterized by a deviant lifestyle and an inability to regulate emotion. A sample of 29 male inmates was administered the Coping Inventory for Stressful Situations (CISS), the Buss–Perry Aggression Questionnaire (BPAQ), the Psychopathy Checklist – Revised (PCL-R), the Mayer–Salovey–Caruso Emotional Intelligence Test (MSCEIT), and five dichotomous items that are converged into the Criminal Behavior Index (CBI). Correlation analysis showed a complex pattern of relationships among the variables. The MSCEIT Experiential area of EI together with CISS Emotion-oriented Coping and PCL-R Social Deviance are found to significantly predict the CBI. The results offer promising findings for the assessment of the relationship between personality traits, emotional abilities and criminal behavior across the life span. Furthermore, the results suggest that EI is an important feature for implementing prevention programs of criminal behavior and recidivism.